2015
DOI: 10.1097/pcc.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Errors in the Pediatric and Neonatal ICU

Abstract: Diagnostic errors in PICU/neonatal ICU populations are most commonly due to infection. Further research is needed to better quantify pediatric intensive care-related misdiagnosis and to define potential strategies to reduce their frequency or mitigate misdiagnosis-related harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 36 publications
1
39
0
10
Order By: Relevance
“…13 Es motivo de preocupación la marcada declinación de su práctica en el mundo y, particularmente, en nuestro país. Publicaciones de la Sociedad Argentina de Pediatría reflejan la magnitud del problema en artículos y editoriales con títulos tales como "Volver a la autopsia o seguir ignorando la verdad".…”
Section: Discussionunclassified
“…13 Es motivo de preocupación la marcada declinación de su práctica en el mundo y, particularmente, en nuestro país. Publicaciones de la Sociedad Argentina de Pediatría reflejan la magnitud del problema en artículos y editoriales con títulos tales como "Volver a la autopsia o seguir ignorando la verdad".…”
Section: Discussionunclassified
“…In a recent systematic review, Custer et al (16) found major diagnostic errors (Goldman classes 1 and 2) in 19.6% of autopsies in the PICU and neonatal ICU setting. Our study identified missed major diagnoses in 21 of 32 autopsies (66%).…”
Section: Discussionmentioning
confidence: 99%
“…Wherever the possibility of error was raised, we analyzed whether it met with participant consensus. Error categories included ventilator, invasive (e.g., vascular) device, medical or surgical procedure, infection, drugs, miscommunication (with patient/parents or between staff), and diagnosis (9,16,17). We then attributed to each error the most appropriate root cause, whether individual or system-based, such as organization, interface issues, milieu, and equipment dysfunction (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The marked decline in autopsies worldwide is a cause for concern, especially in Argentina. Publications of the Argentine Society of Pediatrics reflect the size of this problem in an editorial comment titled Going back to autopsy or continuing to ignore the truth.…”
mentioning
confidence: 99%